Fungsi Budgeting Badan Anggaran DPRD ‎Kota dalam Prespektif Fiqh Siyasah - Abdul Rajab (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This paper wants to reveal two things: (1) the agency's role in the budget of the city parliament performs the function of budgeting; and (2) the views of Fiqh Siyasah about the role of the Parliament budget city/county in realizing the function of budgeting. In the end of this paper concluded that, first, the DPRD budget agency has carried out the duties and functions that have been set by the Act. No. 27 of the MPR, DPR, DPD and DPRD 2009, to discuss and approve draft local regulations regarding the budget revenue and expenditure Surabaya proposed by the mayor. Second, the city parliament budget agency in the review of Fiqh Siyasah is as ahl al-halli wa al-'aqd must be trustworthy in carrying out tasks that have been given of the people, in relation to the budget management functions as an institution of shura which represents the aspirations and will of the people.Â Abstrak: Tulisan ini ingin mengungkap dua hal, yaitu: (1) peran badan anggaran DPRD kota/kabupaten dalam melakukan fungsi budgeting; dan (2) pandangan Fiqh Siyasah tentang peran badan anggaran DPRD kota/kabupaten dalam merealisasikan fungsi budgeting. Dalam akhir tulisan ini dismpulkan bahwa, pertama, badan anggaran DPRD telah melaksanakan tugas dan fungsi yang telah diatur oleh UU. No. 27 tentang MPR, DPR, DPD, dan DPRD tahun 2009, membahas dan memberikan persetujuan rancangan peraturan daerah mengenai anggaran pendapatan dan belanja daerah Kota Surabaya yang diajukan oleh walikota. Kedua, badan anggaran DPRD kota/kabupaten dalam perspektif Fiqh Siyasah adalah ahl al-halli wa al-'aqd harus amanah dalam melaksanakan tugas yang telah diberikan rakyat, dalam kaitannya dengan pengelolaan anggaran berfungsi sebagai lembaga syura yang mewakili aspirasi dan kehendak rakyat.